Diffuse pacemaker mechanism with distinctive organization drives pulsation in the octocoral Xenia umbellata - Elinor Nadir; Yehuda Benayahu; Maya Ofek-Lalzar; Tslil Gabrieli; Tamar Lotan (Proceedings of the National Academy of Sciences, 2025)
The unique, hypnotic pulsation behavior of certain soft corals of the Xeniidae family, the result of rhythmic opening and closing of their tentacles, has fascinated scientists since the 18th century. Repetitive motion is regulated by autonomous neural circuits known as pacemakers or central pattern generators. However, little is known about such circuits in nonbilaterian organisms like corals. In this report, Xenia umbellata , a fast-growing octocoral, served as a model organism to study the muscular and neural mechanisms of pulsation. Leveraging this coral’s rapid regeneration ability, we tested somatic regrowth and pulsation recovery following oral disc amputation. Transcriptomic analysis upon transitioning from nonpulsation to intermediate and synchronized pulsation during regeneration demonstrated shared pulsation-related genes in X. umbellata and bilaterians, suggesting an evolutionarily conserved rhythmic machinery. Pharmacological interference experiments supported transcriptomic findings, showing that acetylcholine regulates pulsation and anoctamin channels affect pacemaker rhythm. Interestingly, in the intermediate pulsation phase tentacles could pulsate individually without synchronization, suggesting the development of separate pacemakers. At the synchronized pulsation phase a dense nerve net developed around the mouth opening and overlapping muscle fibers between tentacles, providing the mechanisms for tentacle synchronization. However, when polyp tentacles were cut into small pieces, the fragments remained alive and each retained independent pulsation, revealing a unique pacemaker system driven by a diffuse nerve network lacking any centralized control. This finding uncovers a mechanism of rhythmic behavior generation in nonbilaterian animals, which could represent either a lineage-specific innovation or an ancient origin for more centralized control.